Development and use of Сherenkov-type detectors for measurements of fast electrons in tokamaks - Rabiński, M.; Jakubowski, L.; Żebrowski, J.; Sadowski, M.J.; Malinowski, K.; Mirowski, R.; Jakubowski, M.; Plyusnin, V.V.; Lotte, Ph.; Pascal, J-Y. (Вопросы атомной науки и техники, 2012)
The paper reports on progress in design and use of novel detectors for experimental studies of fast (run-away and ripple-born) electrons in various experiments of the tokamak type. The idea of the use of a Cherenkov effect for direct on-line measurements of the fast electrons within tokamaks was presented by scientists from the NCBJ (former IPJ) several years ago. Successive efforts led to the development of prototype detector heads equipped with diamond or aluminium nitrate (AlN) crystals, which were shielded with very thin metal filters in order to eliminate the visible light from plasma and to enable a rough energy analysis of electrons. Those Cherenkov radiators were coupled through optical-fibre cables with fast photomultipliers. Those prototypes were applied for test measurements within the CASTOR experiment in Prague, and later in the ISSTOK device in Lisbon, but the main aim remained to develop the Cherenkov detectors for the TORE-SUPRA experiment in Cadarache. В этой статье представлен прогресс в разработке и использовании новаторских детекторов для экспериментального исследования быстрых (убегающих и генерируемых на неоднородностях) электронов в различных экспериментах на токамаке. Идея использования эффекта Черенкова для прямых измерений быстрых электронов в режиме реального времени в токамаке был представлен учеными из НЦЯП (бывший ИЯП) несколько лет назад. Последовательные усилия привели к разработке прототипа детекторных головок оснащенного кристаллами алмаза или нитрата алюминия (AlN), которые были покрыты очень тонкими металлическими фильтрами для исключения влияния видимого света из плазмы и позволяющими грубо оценить энергию электронов. Эти счетчики Черенкова были соединены через волоконно-оптические кабели с быстрыми ФЭУ. Эти прототипы были применены для тестовых измерений в экспериментах на CASTOR в Праге, а затем в Лиссабоне на установке ISSTOK, но главной целью остается разработка детекторов Черенкова для экспериментов на Tore-Supra в Кадараше. У цій статті йдеться про прогрес у розробці та використанні новаторських детекторів для експериментального дослідження швидких (утеклих і тих., що генеруються на неоднорідностях) електронів в різних експериментах на токамаці. Ідея використання ефекту Черенкова для прямих вимірювань швидких електронів в режимі реального часу в токамаке був представлений вченими з НЦЯП (колишній ІЯП) кілька років тому. Послідовні зусилля привели до розробки прототипу детекторних головок оснащеного кристалами алмазу або нітрату алюмінію (AlN), які були покриті дуже тонкими металевими фільтрами для виключення впливу видимого світла з плазми і дозволяють грубо оцінити енергію електронів. Ці лічильники Черенкова були з'єднані через волоконно-оптичні кабелі з швидкими ФЕУ. Ці прототипи були застосовані для тестових вимірювань в експериментах на CASTOR в Празі, а потім в Лісабоні на установці ISSTOK, але головною метою залишається розробка детекторів Черенкова для експериментів на Tore-Supra в Кадараші.